2018
DOI: 10.1371/journal.pone.0196645
|View full text |Cite
|
Sign up to set email alerts
|

More than a feeling: Autonomous sensory meridian response (ASMR) is characterized by reliable changes in affect and physiology

Abstract: Autonomous Sensory Meridian Response (ASMR) describes the experience of tingling sensations in the crown of the head, in response to a range of audio-visual triggers such as whispering, tapping, and hand movements. Public interest in ASMR has risen dramatically and ASMR experiencers watch ASMR videos to promote relaxation and sleep. Unlike ostensibly similar emotional experiences such as “aesthetic chills” from music and awe-inspiring scenarios, the psychological basis of ASMR has not yet been established. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
258
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(300 citation statements)
references
References 54 publications
28
258
2
3
Order By: Relevance
“…Piloerection during chills is innervated by the sympathetic nervous system (Lindsley and Sassaman, 1938; Craig, 2005). There is no consensus that the parasympathetic nervous system is involved in the ASMR (Poerio et al, 2018). A profound emotional experience, such as weeping, sometimes arises in response to music-induced chills (Sloboda, 1991; Panksepp, 1995; Mori and Iwanaga, 2017), but not in response to the ASMR.…”
Section: Discussionmentioning
confidence: 99%
“…Piloerection during chills is innervated by the sympathetic nervous system (Lindsley and Sassaman, 1938; Craig, 2005). There is no consensus that the parasympathetic nervous system is involved in the ASMR (Poerio et al, 2018). A profound emotional experience, such as weeping, sometimes arises in response to music-induced chills (Sloboda, 1991; Panksepp, 1995; Mori and Iwanaga, 2017), but not in response to the ASMR.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear whether the selfreport ratings of tingle intensity are comparable across participants (i.e., is unclear whether a 5/10 rating for one participant reflects the same ASMR intensity as a 5/10 rating from another participant). Future studies should acquire psychophysiological measures such as skin conductance responses and heart rate in order to provide a more valid measure of ASMR intensity (see Poerio et al, 2018). Finally, using a more temporally sensitive neuroimaging technique such as electroencephalography (EEG) or magnetoencephalography (MEG) would allow researchers to more precisely measure the time course of activity during the ASMR experience; specifically, these techniques could measure the location and frequency of neuronal activity immediately prior to and following the onset of ASMR tingles.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Self-report studies has consistently shown that ASMR is associated with a feeling of calm (Barratt & Davis, 2015;Fredborg et al, 2017). However, the psychophysiological data suggest that ASMR is a physiologically arousing experience as well (Poerio et al, 2018). Importantly, this pattern of autonomic activity is distinct from the increased heart rate associated with aesthetic chills such as the frisson experienced during the perception of emotional musical pieces (Benedek & Kaernbach, 2011;Grewe, Kopiez, & Altenmüüller, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations